Indian clinical practice consensus guidelines for the management of oropharyngeal cancer: Update 2022 - Noronha, Vanita; Prabhash, Kumar; Babu, K Govind; Chaturvedi, Pankaj; Kuriakose, Moni; Birur, Praveen; Anand, Anil K; Kaushal, Ashish; Mahajan, Abhishek; Syiemlieh, Judita; Singhal, Manish; Gairola, Munish; et al. (Cancer research, statistics, and treatment (Online), 2024)
The aim of oropharyngeal cancer treatment should be to treat the disease while preserving speech and swallowing abilities. Early-stage disease is generally treated with surgery/radiotherapy (RT). A combination of chemotherapy and RT should be considered instead of RT alone for patients with locally advanced disease. Patients with locally advanced resectable disease can be treated with transoral or open resection of the primary + ipsilateral/bilateral neck dissection ± adjuvant chemoradiotherapy (CTRT)/adjuvant RT. In unresectable locally advanced disease, sequential induction chemotherapy (TPF [docetaxel, cisplatin, fluorouracil]) followed by locoregional treatment with RT or CTRT can be considered. Adding targeted therapies like nimotuzumab to cisplatin-based CTRT in locally advanced head-and-neck squamous cell carcinoma improves the progression-free survival, locoregional control, and disease-free survival without negatively impacting the quality of life.